ANALISIS TATA KELOLA SISTIM DRAINASE YANG BERKELANJUTAN BERBASIS PARTISIPASI MASYARAKAT (Studi Kasus di Perumahan Duta Green City Kota Pekanbaru Provinsi Riau) (Jurnal Kajian Lingkungan, 2014)
The research of drainase system was conducted in Desember 2011 in Duta Green City residential of subdistrict Simpang Tiga, sub-district office Marpoyan Damaiof Pekanbaru, Riau Province. The study applied to Desciptive Evaluatif, the method treatments to seek the Evaluation of the existence object. Research on governace of community-based drainage system aims to look at some important aspects that relate directly to the drainage network system in the residential Duta green City of Pekanbaru Riau Province. After doing research result obtained among other, performance drainage network in good condition, public understanding of sustainable drainage network system has been well 85,95 % people understand the function of sustainable drainage systems, public awarneness of Duta Green City to good drainage network system management, 90,70 % people are always and maintenance of drainage.Keywords: Duta Green City, Drainase System, Comprehension Human